Ruxolitinib inhibits poly(I:C) and type 2 cytokines‐induced CCL5 production in bronchial epithelial cells: A potential therapeutic agent for severe eosinophilic asthma. Issue 2 (3rd February 2021) - Sada, Mitsuru; Watanabe, Masato; Inui, Toshiya; Nakamoto, Keitaro; Hirata, Aya; Nakamura, Masuo; Honda, Kojiro; Saraya, Takeshi; Kurai, Daisuke; Kimura, Hirokazu; Ishii, Haruyuki; Takizawa, Hajime
Abstract: Rationale: Severe eosinophilic asthma is characterized by airway eosinophilia and corticosteroid‐resistance, commonly overlapping with type 2 inflammation. It has been reported that chemokine (C‐C motif) ligand 5 (CCL5) is involved in the exacerbation of asthma by RNA virus infections. Indeed, treatment with a virus‐associated ligand and a T helper type 2 cell (Th2) cytokine can synergistically stimulate CCL5 production in bronchial epithelial cells. We aimed to evaluate the mechanisms underlying CCL5 production in this in vitro model and to assess the potential of Janus kinase 1 (JAK1) as a novel therapeutic target via the use of ruxolitinib. Methods: We stimulated primary normal human bronchial epithelial (NHBE) cells and BEAS‐2B cells with poly(I:C) along with interleukin‐13 (IL‐13) or IL‐4, and assessed CCL5 production. We also evaluated the signals involved in virus‐ and Th2‐cytokine‐induced CCL5 production and explored a therapeutic agent that attenuates the CCL5 production. Results: Poly(I:C) stimulated NHBE and BEAS‐2B cells to produce CCL5. Poly(I:C) and IL‐13 increased CCL5 production. Poly(I:C)‐induced CCL5 production occurred via the TLR3–IRF3 and IFNAR/JAK1–phosphoinositide 3‐kinase (PI3K) pathways, but not the IFNAR/JAK1–STATs pathway. In addition, IL‐13 did not augment poly(I:C)‐induced CCL5 production via the canonical IL‐13R/IL‐4R/JAK1–STAT6 pathway but likely via subsequent TLR3‐IRF3‐IFNAR/JAK1‐PI3K pathways. JAK1 was identified to be a potential therapeutic target for severe eosinophilic asthma. The JAK1/2 inhibitor, ruxolitinib, was demonstrated to more effectively decrease CCL5 production in BEAS‐2B cells than fluticasone propionate. Conclusion: We have demonstrated that JAK1 is a possible therapeutic target for severe corticosteroid‐resistant asthma with airway eosinophilia and persistent Th2‐type inflammation, and that ruxolitinib has potential as an alternative pharmacotherapy. Abstract : First, we focused on whether treatment with a virus‐associated ligand and type‐2 cytokine can synergistically stimulate CCL5 production in bronchial epithelial cells, in which we confirmed the synergistic effect. Second, we evaluated the mechanisms underlying the synergistical CCL5 production and found that the JAK1 is a novel therapeutic target for severe eosinophilic asthma. Finally, we have demonstrated that ruxolitinib is a potential therapeutic agent for severe corticosteroid‐resistant asthma with airway eosinophilia and persistent Th2‐type inflammation.